Educational technology for multidisciplinary training for managing waiting lists for elective patients - Rosa Ladi Lisbôa; Kaihara de Freitas Furtado; Vitória Silva da Rosa; Caroline Schacker Evangelista; Adriana Aparecida Paz (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to construct and assess an educational technology for managing patient waiting lists for multidisciplinary training. Methods: study supported by Instructional Design - ADDIE model, whose stages of construction of educational technology were developed in the form of a multi-professional training course. Its respective content assessment was carried out by a committee of experts from 2021 to 2022. The analysis occurred based on the proportion of content adequacy with 95% Confidence Interval. Results: seventeen products were created as educational technology learning objects: five storyboards; four videos; three comic books; two pedagogical action plans; a mind map; and a YouTube® playlist. Nine experts assessed content adequacy, which reached 0.89. Conclusions: this educational technology contributes to the performance of professionals who manage waiting lists by reducing inequalities, alleviating differences, in addition to promoting equity in care and good health for patients in the Brazilian Health System.